1982
DOI: 10.1111/j.1476-5381.1982.tb09196.x
|View full text |Cite
|
Sign up to set email alerts
|

ALTERATION IN THE LEVEL OF ENDOGENOUS HYPOTHALAMIC PROSTAGLANDINS INDUCED BY Δ9‐TETRAHYDROCANNABINOL IN THE RAT

Abstract: Whole brain and regional brain levels of prostaglandin E2 (PGE2)‐like material have been determined following administration of Δ9‐tetrahydrocannabinol (Δ9‐THC) in rats. Intravenous administration of Δ9‐THC 2 mg/kg, resulted in marked behavioural changes and hypothermia. The behavioural changes consisted mainly of catatonia (most apparent at 30 min after administration of Δ9‐THC), followed by sedation (most evident at 60 min). Hypothermia was marked from 30 min after administration of Δ9‐THC. Δ9‐THC did not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…There was no difference in the size of increase in the concentrations of either PG, induced by THC. The augmented PG levels declined markedly by 8 h and had returned to normal by 24 h. There appears to be only one earlier report on the in vivo effect of THC on central PGs (Coupar and Taylor 1982), who reported that it does not alter PGE2-1ike activity in rat brain, apart from the hypothalamus where a small decrease was evidenced. The workers used a bioassay technique.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There was no difference in the size of increase in the concentrations of either PG, induced by THC. The augmented PG levels declined markedly by 8 h and had returned to normal by 24 h. There appears to be only one earlier report on the in vivo effect of THC on central PGs (Coupar and Taylor 1982), who reported that it does not alter PGE2-1ike activity in rat brain, apart from the hypothalamus where a small decrease was evidenced. The workers used a bioassay technique.…”
Section: Discussionmentioning
confidence: 95%
“…A survey of the relevant literature reveals that no attempt has been made to investigate the effect of THC on the levels of central PGs, apart from the work of Coupar and Taylor (1982), who have reported that THC does not alter "PGE/-like" activity of most rat brain areas except the hypothalamus, where a small increase was noted. These workers used a bioassay procedure for PGE2 estimation.…”
mentioning
confidence: 99%
“…Therefore, at least part of the suppressive action of THC on the release of LH and GH may be mediated by suppression of LHRH release plus stimulation of SRIF release. It will be of interest to determine whether the In earlier studies, intravenous administration of THC at doses that produced marked behavioral changes, including catatonia sedation, plus hypothermia produced a significant reduction of PGE2-like material in the hypothalamus but not in other brain areas, which suggested that the mechanism by which THC alters hypothalamic hormone release might be via a decrease of hypothalamic PG synthesis (11,12). The current studies provide evidence that the mechanism for the suppression of LHRH release is the suppression of not only the synthesis of PGs but also their release.…”
Section: Discussionmentioning
confidence: 99%
“…They postulated that PGE2 was involved with the catatonia produced by THC. Coupar and Taylor (1982) injected tethahydrocannabinol in rats resulting in catatonia. The results of the methods employed in this study did not support the suggestions that THC increases the level of PGE2-like material.…”
Section: Discussionmentioning
confidence: 99%